Evaluating the Quality of Sentence Structures, Citations and References in Journal Articles: A Case Study in the Faculty of Mathematics and Science and the Faculty of Engineering - Analisti, Dea (2016)
This qualitative descriptive study attempts to investigate the sentence types and to evaluate the sentence logic, and the appropriateness of citations and references in the journal articles written by lecturers from the Faculty of Mathematics and Science and the Faculty of Engineering. The sentence analysis is based on the frameworks proposed by Alwi, Dardjowidjojo, Lapoliwa, and Moeliono (2003) and Oshima and Hogue (2007). Meanwhile, the analysis of citations and references is based on APA style (6th edition). The results of the sentence analysis show that complex sentences are the most frequent sentence type found in the journal articles. Moreover, the quality of sentence logic in the journal articles is good since most of sentences are written correctly and well structured. Citations and references analysis regarding the characteristics of reference sources show several important results: 1) books are the most frequent reference sources used in the journal articles, 2) the most common language used in the journal articles is Indonesian language and 3) the sources published in 6 - 10 years are the most frequent source used in the journal articles. Regarding the appropriateness of citations and references, citations and references are mostly written inappropriately. In addition, mistakes related to the use of mechanics are the most common citation mistake and mistakes related to title are the most common reference mistake found in the journal articles. Overall, it can be concluded that the journal articles are good regarding the sentence logic, but they need more improvement regarding citations and references. Keywords: Sentence Types, Sentence Logic, Appropriateness, Citations, References. Studi kualitatif deskriptif ini mencoba untuk menginvestigasi jenis kalimat dan mengevaluasi kelogisan kalimat, dan kelayakan kutipan dan rujukan pada artikel jurnal yang ditulis dosen-dosen Fakultas Matematika dan Ilmu Pengetahuan Alam dan Fakultas Teknik. Analisis kalimat berdasarkan kerangka dari Alwi, Dardjowidjojo, Lapoliwa, dan Moeliono (2003) dan Oshima dan Hogue (2007). Semantara itu, analisis kutipan dan rujukan berdasarkan APA (Edisi 6). Hasil dari analisis kalimat menunjukan bahwa kalimat majemuk bertingkat sebagai jenis kalimat yang paling sering digunakan. Selain itu, kualitas kelogisan kalimat pada artikel jurnal adalah baik karena kebanyakan kalimat ditulis secara benar dan terstuktur secara baik. Hasil dari analisis kutipan dan rujukan berkenaan dengan sifat-sifat sumber rujukan menunjukan beberapa hasil penting: 1) buku menjadi sumber yang paling sering digunakan dalam artikel jurnal, 2) sumber rujukan berbahasa Indonesia menjadi sumber yang paling sering digunakan di dalam artikel jurnal, dan 3) sumber yang dipublikasikan dalam waktu 6 - 10 tahun menjadi sumber yang paling sering digunakan dalam artikel jurnal. Berkenaan dengan ketepatan kutipan dan rujukan, kutipan dan rujukan kebanyakan ditulis secara tidak tepat. Selain itu, kesalahan yang berkaitan dengan penggunaan mekanis menjadi kesalahan yang paling umum dalam kutipan dan kesalahan yang berkaitan dengan judul menjadi kesalahan yang paling umum dalam rujukan. Secara keseluruhan, dapat disimpulkan bahwa artikel jurnal bagus berkenaan dengan kelogisan kalimatnya tetapi artikel jurnal membutuhkan banyak perbaikan berkenaan dengan kutipan dan rujukan. Kata Kunci: Jenis Kalimat, Kelogisan Kalimat, Ketepatan, Kutipan, Rujukan